Outraged : why we fight about morality and politics and how to find common ground - Gray, Kurt James (Pantheon Books, 2025)
"In this insightful tour of the moral mind, Gray provides a groundbreaking new framework for our moral foundations that rewrites our understanding of where moral judgments come from, and how we can overcome the feelings of outrage that so often divide us"--